Natural trypanocidal product produced by endophytic fungi through co-culturing - do Nascimento, Jainara Santos; Silva, Felipe Moura; Magallanes-Noguera, Cynthia Alejandra; Kurina-Sanz, Marcela; Dos Santos, Elda Gonçalves; Caldas, Ivo Santana; Luiz, Jaine Honorata Hortolan; Silva, Eliane de Oliveira (Folia microbiologica, 2020)
Endophytic fungi live inside vegetal tissues without causing damage to the host plant and may provide lead compounds for drug discovery. The co-culture of two or more endophytic fungi can trigger silent gene clusters, which could lead to the isolation of bioactive compounds. In this study, two endophytic strains isolated from Handroanthus impetiginosus leaves, identified as Talaromyces purpurogenus H4 and Phanerochaete sp. H2, were grown in mixed and axenic cultures. The meroterpenoid austin was detected only in the extracts from the mixed culture. Once isolated, austin displayed very interesting trypanocidal activity, with an IC50 value of 36.6 ± 1.2 μg/mL against Trypanosoma cruzi in the epimastigote form. The results obtained highlight the importance of the co-culturing of endophytic fungi to obtain natural bioactive products. The findings also enhance our understanding of the ecological relationships between endophytic fungi.
Keywords: listy rostlin; Coculture Techniques; endofyty; kokultivační techniky; Plant Leaves; Trypanosoma cruzi; terpeny; Trypanocidal Agents; Endophytes; Terpenes; Phanerochaete; Tabebuia; Talaromyces; trypanocidální látky